2005
DOI: 10.1177/0885066605275391
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Rapidly Progressive Interstitial Pneumonitis Associated With Amyopathic Dermatomyositis and CD8 T Lymphocytes

Abstract: A patient with amyopathic dermatomyositis associated with fatal rapidly progressive interstitial pneumonitis resistant to therapy is described. Pathologic examination of a transbronchial lung biopsy specimen showed diffuse alveolar damage and nonspecific interstitial pneumonia-organizing pneumonia-like findings. Bronchoalveolar lavage fluid contained many CD8+ lymphocytes, considered to be cytotoxic T cells. Analysis of bronchoalveolar lavage fluid in this case may provide prognostically and pathogenetically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
2
15
1
Order By: Relevance
“…Regarding the anti-Jo-1 antibody, only one patient with chronic ILD-ADM had this antibody among the present ILD-ADM study. To date, several studies have reported a low incidence of anti-Jo-1 antibody in ILD-ADM patients [11][12][13][17][18][19]. The current results were consistent with those studies.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Regarding the anti-Jo-1 antibody, only one patient with chronic ILD-ADM had this antibody among the present ILD-ADM study. To date, several studies have reported a low incidence of anti-Jo-1 antibody in ILD-ADM patients [11][12][13][17][18][19]. The current results were consistent with those studies.…”
Section: Discussionsupporting
confidence: 92%
“…To date, little is known about the BAL findings of ILD-ADM. Two reports from Japan demonstrated an increase of BALF lymphocytes and neutrophils in acute/subacute ILD-ADM [11,12]. The present study showed that the BAL findings differed between the two forms.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations